Selection of reference genes for RT-qPCR analysis of Phenacoccus solenopsis (Hemiptera: Pseudococcidae) sex-dimorphic development - Lu-ying ZHENG; Zhi-jun ZHANG; Jin-ming ZHANG; Xiao-wei LI; Jun HUANG; Wen-cai LIN; Wei-di LI; Chuan-ren LI; Yao-bin LU (Journal of Integrative Agriculture, 2019)
Mealybugs, such as Phenacoccus solenopsis, are highly sexually dimorphic. Winged adult males present such remarkable morphological differences from females that, to the untrained eye, conspecific adults of both sexes of P. solenopsis may be considered as two different insect species. A method to investigate sex-dimorphic mechanisms is by evaluating gene expression using RT-qPCR. However, the accuracy and consistency of this technique depend on the reference gene(s) selected. In this study, we analyzed the expression of 10 candidate reference genes in male and female P. solenopsis at different development stages, using common algorithms including the ΔCt method, NormFinder, geNorm, BestKeeper, and a web-based analysis tool, RefFinder. The results showed that EF1-β, RP-L32 and RP-18S were selected as the most stable genes by both the ΔCt method and NormFinder; TUB-α was the most stable gene identified by BestKeeper; and RP-L40 and RP-L32 were the most stable genes ranked by geNorm. RefFinder, a comprehensive analysis software, ranked the ten genes and determined EF1-β and RP-L32 as the most suitable reference genes for the various developmental stages in male and female P. solenopsis. Furthermore, the two most suitable reference genes were validated by examining expression of the juvenile hormone acid O-methytransferase (JHAMT) gene. Results of the validation portion of the study showed that JHAMT expression was sex-biased towards males and exhibited a dynamic and classic expression pattern among the P. solenopsis developmental stages. The results can help further our knowledge on the molecular mechanisms underlying sexual dimorphic development in P. solenopsis.